Ontology for mushroom growing operations - Gautam, Y; Singh, A J (Mushroom Research, 2011)
Ontology, a formal representation of knowledge as a set of concepts within a domain, forÂ mushroom growing operations is defined. The mushroom growing operations have beenÂ grouped into five categories viz., Spawing, Composting, Crop management, Har Pro marketÂ and General.